Why Does Discrimination Against Indigenous Beliefs Persist in Indonesia? - Nurwansyah, Agus; Hidayat, Taufiq (Institut Agama Islam Negeri Kerinci, 2024)
The number of adherents of traditional beliefs in Indonesia is approximately 12 million, spread across 27 provinces. However, despite this significant number, they have not yet been recognized by the state as equal to formal religions in the religion column on their Identity Cards (KTP). This study employs a descriptive-qualitative method based on a critical paradigm, using Antonio Gramsci’s theory of hegemony as its analytical framework. The findings reveal that state hegemony began with the consensus to label traditional beliefs as